Are owners chalk and cheese in the context of dividend smoothing asymmetry? - Zahid Ali; Zahid Ali; Yang Hanming; Wu Zhongxin; Shuaib Ali (Frontiers in Psychology, 2022)
The study analyzes the impact of ownership structure on dividend smoothing via the lens of agency and information asymmetry theory. The study also investigates the impact of ownership on dividend smoothing in the unexamined asymmetric context Dividend smoothing is measured via speed of adjustment and relative volatility. The study documents that higher individual, management, and institutional ownerships are positively associated with increased dividend smoothing. Consistent with the rental hypothesis in foreign-owned firms smooth less also concentrated firms bear with cuts and omissions. Foreign ownership has the opposite impact on dividend smoothing in adjusting dividends from below and above i.e., always prefer high dividends. Individual ownership has also exhibited a different impact in smoothing from below and above. Institutional owners avoid cuts and omissions and negatively affect SOA (smooth more) in case of adjusting dividends from above. Ownership concentration is negatively associated with dividend smoothing irrespective of whether the firm is smoothing from above or below. In contrast, management ownership negatively affected SOA in adjusting from above or below. Family firms in Pakistan smooth more to win minor shareholders' trust and signal that they sacrifice their private benefits to reduce the type II agency problem. Finally, the authors found a negative association between dividend smoothing and corporate governance quality. Over all the findings of the current study provides insight to the investors and regulators by offering dividend smoothing as an alternative monitoring mechanism to corporate governance.